Chronic right lung abscess with empyema thoracic presenting as continuous high-grade fever: A case report - Sonia; Kusum Kumari; Neetu Kataria; Sudhir K. Shahi; C. Vasantha Kalyani (Journal of Family Medicine and Primary Care)
A lung abscess is a microbial infection of the lungs. An empyema is an accumulation of pus in the pleural space that increases after infection of either lung or pleura generally. The sign of empyema is similar to that of lung abscess in that the patient has complaints of high-grade fever, chest pain, and productive cough. Here, we present the report of a patient who was admitted with high-grade fever, which could not be treated despite aggressive medical treatment due to underlying lung pathology. A 30-year-old woman started having right-sided chest pain; subsequently, she developed fever, which was continuous and high grade in character, for which she visited a local doctor. Right-sided intercostal drainage was done in that hospital, but neither too much drain came out nor she experienced relief in symptoms. Then, she was referred to a tertiary care center in Delhi for further treatment. She got re-evaluated there. During hospitalization, despite treatment with intravenous (IV) paracetamol and third-generation IV antibiotics, the fever did not come down, and hence she was planned for emergency posterior lateral thoracotomy to deal with the underlying pathology causing persistent high-grade fever. High-risk consent was taken for right side thoracotomy and patient was operated in a febrile condition. She was discharged on the third postoperative day with the chest tube in situ. The fever could not be treated for last 3 months despite aggressive medical treatment. Evacuation of pus from the pleural cavity was mandatory here because it was the primary focus to reduce the high-grade fever of patient.